Pengaruh Harga, Kualitas Produk dan Lokasi Terhadap Pembelian Konsumen - Gilang Mardiyaningsih; Sujiono Sujiono; Siti Chamidah (ASSET: Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine "The Effect of Price, Product Quality and Location on Purchasing Decisions of Consumers on Reog Steak Chicken Ponorogo)". The population in this study is all consumers who buy at RSC. The number of samples taken was 93 respondents. Data and results of respondents' answers were processed using the SPSS 16. The results showed that the price (X1), product quality (X2), and location (X3) variables had a significant effect on purchasing decisions at the RSC. The test results of the variable which is the most dominant influence on purchasing decisions are product quality. From the results of the study are expected to be beneficial to all parties